Validation of a suite of biomarkers of fish health in the tropical bioindicator species, tambaqui (Colossoma macropomum) - Sadauskas-Henrique, Helen; Duarte, Rafael Mendonça [UNESP]; Gagnon, Marthe Monique; Almeida-Val, Vera Maria Fonseca (Elsevier, 2017)
Here we explore the dose-dependent response of the tropical fish tambaqui (Colossoma macropomum) to intraperitoneal injection of benzo[a]pyrene (BaP) at doses of 0 (carrier control), 1, 10, 100 and 1000 μmolar BaP Kg−1 Hepatic ethoxyresorufin-O-deethylase (EROD) activity showed a bell-shaped dose-dependent response curve, where the highest injected BaP dose caused enzyme inactivation. Activities of hepatic catalase (CAT) and superoxide dismutase (SOD) increased at the highest dose relative to the carrier control group. Lipid peroxidation (LPO), serum-sorbitol dehydrogenase (s-SDH) and DNA damage in blood cells were higher for all BaP doses when compared to the carrier control group. At high dosage, the production of BaP metabolites was paralleled by induced activity of the antioxidant enzyme SOD, and high levels of DNA damage in blood cells. In a similar way, high LPO was concomitant to elevated s-SDH in the bloodstream, suggesting that lipid peroxidation caused the loss of membrane integrity and leakage of s-SDH from hepatocytes into the bloodstream. These biomarkers were also positively co-correlated. The results demonstrate the potential use of a suite of biomarkers for tambaqui living in contaminated tropical aquatic environments. In particular, we recommend the analysis of DNA damage in blood cells, as this was highly correlated with all other biomarkers.
Keywords: BaP; Biomarkers; CAT; EROD activity; GST; LPO; s-SDH; SOD; Tambaqui